Waste Management of Innovation Production Through The Printing Block Printing Plate Workshop Using The Design Thinking Approach - Hafildah, Nora; Widiatmoko Soewardikoen, Didit; Azhar, Hanif; Nur Hadiansyah, Mahendra (Sahabat Publikasi, 2024)
The waste problem in Indonesia is a problem that has not been resolved to date; this hurts the surrounding environment, one of which is 23.3 million tonnes annually produced from 202 districts or cities, of which only 15 are appropriately managed. 6 million tons annually. Therefore, it is necessary to process plastic waste to minimize the accumulation of plastic waste and its impact on the environment (Amanullah. G, 2023). Olah Plastic is one of the MSMEs located in Bandung that processes plastic waste into products. However, Olah Plastic has a problem in the form of remaining unprocessed production waste, so product innovation is needed that can minimize production waste and activities that can increase public knowledge about processing. plastic waste. The results of this research are block printing plates made from the remaining waste from Olah Plastic production, where the printing plates will be used as media in workshops to increase public awareness regarding the negative impact of plastic waste on the environment, which still has selling value